2012
DOI: 10.1111/j.1468-1293.2012.01056.x
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and use of nonoccupational HIV post‐exposure prophylaxis among people receiving rapid HIV testing in Spain

Abstract: ObjectivesThis paper examines the awareness and use of nonoccupational HIV post-exposure prophylaxis (nPEP) in Spain, and the factors that influence this awareness. MethodsBetween June 2009 and July 2010, a mobile unit offered free, rapid HIV tests in a number of Spanish cities. A total of 2545 people were passively recruited and tested, and answered a self-administered questionnaire containing sociodemographic, behavioural and nPEP-related questions. Bivariate and multivariate analyses were performed, stratif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
1
10

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 16 publications
3
27
1
10
Order By: Relevance
“…In France, 70% of individuals reported the knowledge of PEP, mainly MSM [29]. It has been recently reported that awareness of PEP increases with the number of' previous HIV tests [30]. Between 2008 and 201l, HIV prevention campaigns were conducted in France, including HIV-testing for the general population as well as for those with high risk behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…In France, 70% of individuals reported the knowledge of PEP, mainly MSM [29]. It has been recently reported that awareness of PEP increases with the number of' previous HIV tests [30]. Between 2008 and 201l, HIV prevention campaigns were conducted in France, including HIV-testing for the general population as well as for those with high risk behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…PEPSE provision is not recommended in cases where the index individual is HIV positive with a viral load of <200copies/ml, regardless of the type of sexual exposure. Convenience samples of HIV negative MSM found that 34% of MSM in Spain and 36% in the USA were aware of PEPSE availability; having a higher number of sex partners was significantly associated (OR 5.1, p=0.02) with higher rates of awareness (387,388). Awareness was higher (52-66%) in MSM living with HIV (389,390).…”
Section: Antiretroviral Post-exposure Prophylaxis For Sexual Exposurementioning
confidence: 93%
“…[19][20][21] However, MSM awareness is greater than other sexual orientations, including women and men who have sex with women. 22 Campaigns and interventions have succeeded to increase PEP awareness in MSM. 23 Injury from discarded needles in the community creates concern for transmission of HIV; however, HIV transmission via community needle-stick injuries (CNSI) has not been documented to date and should be considered extremely low risk, with non-occupational PEP (nPEP) not recommended for these exposures.…”
Section: Introductionmentioning
confidence: 98%